The Effects of 5E Inquiring-Based Learning Management on Grade 7 Students’ Science Learning Achievement - Editor, Sumittra Yonyubon; Jatuporn Khamsong; Wittaya Worapun (Journal of Educational Issues, 2024)
The 5E teaching model is presented as an inquiring-based instructional method that benefits learners by letting them construct their knowledge of the class concepts from what they have learned or experienced. The sole purpose of the studies was to compare grade 7 students’ learning achievement of science before and after learning in the learning management plan designed using the 5E inquiry-based learning. The study was conducted in a quasi-experimental design. The participants were 20 grade 7 students in Thailand. They were selected by a purposive random sampling method. The instruments included a 5E inquiring-based learning management plan and a pre-post learning achievement test. The data were analyzed by percentage, mean score, and standard deviation while the study hypothesis was tested using a paired-samples t-test. The results of the study indicate that the implementation of the 5E inquiry-based learning management plan benefits students’ knowledge of heat in a science class. The study provides pedagogical implications as it illustrated how a learning management plan designed in the 5E inquiry-based teaching model affected a science class. It also contributes to the research in the area as it extended the benefits of the teaching model in teaching concepts of science.